On the nomenclature of the palaemonid names Palaemon spinipes Desmarest, 1817, Palaemon spinipes Schenkel, 1902, and Macrobrachium wallacei Wowor & Ng, 2008 (Crustacea: Decapoda: Caridea) - Ng, Peter K. L.; Wowor, Daisy (Zootaxa, 2011)
Holthuis (1995) commented that there were two forms that have been referred to the widespread Indo-West Pacific Giant Freshwater Prawn Macrobrachium rosenbergii (De Man, 1879), and they should be recognized as subspecies: M. rosenbergii rosenbergii (De Man, 1897) sensu stricto (eastern Indonesia, New Guinea, Australia and Philippines), and M. rosenbergii dacqueti (Sunier, 1925) (Sundaic Southeast Asia, Indochina and South Asia). Wowor & Ng (2007) argued that the two subspecies should be regarded as distinct species – M. rosenbergii (De Man, 1879) and M. dacqueti (Sunier, 1925). They showed that the two species, in addition to their non-overlapping distributions, can be distinguished by the relative height of the rostral base, spination of the second to fifth pereiopods in adults, shape of the fourth thoracic sternite as well as live coloration. However, in doing so, Wowor & Ng (2007) created a major nomenclatural problem, as the species that is widely fished in South and Southeast Asia as well as Indochina, and also extensively cultured throughout the world should actually be known as M. dacqueti and not M. rosenbergii. To minimize taxonomic and nomenclatural confusion, they noted that it would be preferable if the name “M. rosenbergii” could be retained for the commercially more valuable and extensively researched species from Southeast Asia. To this effect, Wowor & Ng (2008) requested the International Commission on Zoological Nomenclature (ICZN) to use its plenary powers to set aside the previous type fixation for Palaemon rosenbergii De Man, 1879 (a holotype female from Andai, New Guinea, in the Nationaal Natuurhistorisch Museum, Leiden, catalogue number RMNH D 1097) and to designate the lectotype specimen of Palaemon dacqueti Sunier, 1925 (a male specimen from Java, Indonesia, in the Nationaal Natuurhistorisch Museum, Leiden, catalogue number RMNH D 1065), as its neotype. This would conserve the name Palaemon rosenbergii De Man, 1879, for the Southeast Asian species. The Commission agreed and ruled that this be done (ICZN 2010, Opinion 2253).